The Impact of Inhaled Ambient Ultrafine Particulate Matter on Developing Brain: Potential Importance of Elemental Contaminants. (December 2019) - Cory-Slechta, Deborah A.; Sobolewski, Marissa; Marvin, Elena; Conrad, Katherine; Merrill, Alyssa; Anderson, Tim; Jackson, Brian P.; Oberdorster, Gunter
Epidemiological studies report associations between air pollution (AP) exposures and several neurodevelopmental disorders including autism, attention deficit disorder, and cognitive delays. Our studies in mice of postnatal (human third trimester brain equivalent) exposures to concentrated ambient ultrafine particles (CAPs) provide biological plausibility for these associations, producing numerous neuropathological and behavioral features of these disorders, including male-biased vulnerability. These findings raise questions about the specific components of AP that underlie its neurotoxicity, which our studies suggest could involve trace elements as candidate neurotoxicants. X-ray fluorescence analyses of CAP chamber filters confirm contamination of AP exposures by multiple elements, including iron (Fe) and sulfur (S). Correspondingly, laser ablation inductively coupled plasma mass spectrometry of brains of male mice indicates marked postexposure elevations of Fe and S and other elements. Elevations of brain Fe and S in particular are consistent with potential ferroptotic, oxidative stress, and altered antioxidant capacity-based mechanisms of CAPs-induced neurotoxicity, supported by observations of increased serum oxidized glutathione and increased neuronal cell death in nucleus accumbens with no corresponding significant increase in caspase-3, in male brains following postnatal CAP exposures. Understanding the role of trace element contaminants of particulate matter AP as a source of neurotoxicity is critical for public health protection.